Representações sociais e experiências da paternidade no contexto da Síndrome Congênita do Vírus Zika - Santos, Gabriella Pereira Leite dos (2019)
In 2015, there was a significant increase in children born with microcephaly, without knowing the cause or the extent of the consequences of the clinical picture. Subsequently, the Ministry of Health registered a treatment for a Congenital Syndrome, due to the wide spectrum of malformations in addition to microcephaly. In view of the seriousness of the situation and the absence of studies on parenting in the context of the malformation, especially the losses of research that address paternity in this context, the present investigative objective study as fatherly experiences and the social representations of the fatherhood of male parents or children were affected by Congenital Zika Virus Syndrome. Seven male parents were interviewed and the results were discussed in two scientific articles, both analyzed from the Content Analysis, type of thematic classification, proposed by Bardin. In the first article, you can select six central categories for analysis and discussion: the discovery of the diagnosis; a parent's experience in health services; the first months of care; the main changes felt by parents after the birth of their child; the difficulties faced; and an evaluation of their own day-to-day experience with the child. In the second article, three central categories were defined: the parents' understanding of Congenital Zika Virus Syndrome and Microcephaly; social representations of paternity and motherhood in this context; and childcare practices. These topics were debated under the theoretical argument of the Theory of Social Representations, proposed by Moscovici. It was found that as social representations about fatherhood in this context are correlated with an experience lived in daily life, as well as with fatherly care practices. The studies showed that the father's experiences are directly related to the social representation of fatherhood, anchored, in turn, in a model of masculinity still hegemonic and in a traditional view of father. Parents believe that they are responsible for the protection of the family and the financial maintenance of the home, assuming a secondary role in childcare practices. However, practices indicative of companionship and expression of affection were found that point to changes regarding paternity. It is estimated that the study may encourage further research on paternity in the context of malformation and disability, in order to give greater visibility to paternal narratives and subsidize health interventions aimed at these actors.